Christians and Jews in the Ottoman Arab world : the roots of sectarianism - Masters, Bruce Alan, 1950- (Cambridge studies in Islamic civilization., 2001)
Masters explores the evolution of Christian and Jewish communities in the Ottoman empire over four hundred years. Early communities lived with the hierarchy of Muslim law, but the nineteenth century marked the beginning of tensions between Muslims and Christians and the twentieth-century rhetoric of religious fundamentalism.